Emerging novel methodologies to understand and strategically target long-lived plasma cells in vaccine design to induce durable immunity - Cusimano, Gina; Staupe, Ryan P.; Sullivan, Nicole L. (Frontiers in Immunology, 2026)
Long-lived plasma cells (LLPCs) are a subset of antibody secreting cells (ASCs) that reside within lymphoid tissues, including the bone marrow (BM) and gut associated lymphoid tissues (GALT), and can secrete antigen-specific antibodies for up to decades or longer. Due to these traits, LLPCs serve as a crucial mediator for durable protective immunity. The signals needed to control the differentiation of LLPCs from naïve B cells, however, are not well understood. Accordingly, it remains a challenge to design vaccines that specifically drive LLPC generation and subsequent antibody durability. In this review, we discuss LLPC generation and heterogeneity following vaccination, vaccine design decisions known to impact immunological memory, and how novel emerging technologies can be used to inform on LLPC biology to enable LLPC targeting vaccine design.